2023
DOI: 10.1332/030557321x16569341758199
|View full text |Cite
|
Sign up to set email alerts
|

Advocacy coalitions, power and policy change

Abstract: This article examines one of the causal concepts in the second advocacy coalition framework (ACF) policy change hypothesis: the notion that major policy change will not occur as long as the advocacy coalition that instated the policy status quo remains ‘in power’ in a jurisdiction. It examines the role of this causal concept in ACF theory. It then reviews existing scholarship on the causal concept, identifying relevant empirical evidence and critically examining how the concept has been operationalised. A stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…By integrating this strong governance and advocacy model with the economic approach, urban river restoration gains a comprehensive framework that addresses the complexities of policy making, implementation, and public buy-in. This multi-pronged strategy not only streamlines the decision-making process but can also build a network of support that sustains the restoration efforts over the long term (Heinmiller et al, 2023). As a result, the transformation of urban rivers from neglected spaces to vibrant ecosystems can become a shared vision that encompasses the interests of various stakeholders, assisting a healthier and more prosperous future for cities and their inhabitants.…”
Section: Discussionmentioning
confidence: 98%
“…By integrating this strong governance and advocacy model with the economic approach, urban river restoration gains a comprehensive framework that addresses the complexities of policy making, implementation, and public buy-in. This multi-pronged strategy not only streamlines the decision-making process but can also build a network of support that sustains the restoration efforts over the long term (Heinmiller et al, 2023). As a result, the transformation of urban rivers from neglected spaces to vibrant ecosystems can become a shared vision that encompasses the interests of various stakeholders, assisting a healthier and more prosperous future for cities and their inhabitants.…”
Section: Discussionmentioning
confidence: 98%
“…Insurance alliances often dominate disaster investigations and can overturn their findings [24]. Moreover, some scholars have verified "the notion that major policy change will not occur as long as the advocacy coalition that instated the policy status quo remains 'in power' in a jurisdiction" [25]. While verifying the impact of political opportunities and the resources of organizations on policy advocacy, it was found that the level of government support, the political connections, and the income of an organization have a positive effect on policy advocacy, but the number of staff, location, and the level of registration have no significant effect [26].…”
Section: Literature Reviewmentioning
confidence: 99%